Penerapan CAC untuk Menganalisis Pengaruh Purchase Intention Pengguna Kosmetik pada Fitur AR - Elisabeth Dian Ladestia Panjaitan; Djohan Gunawan Hasan; Krist Ade Sudiyono (Studi Ilmu Manajemen dan Organisasi, 2025)
Purpose: This study aims to analyze the factors influencing cosmetic purchase intention. The context is the use of augmented reality (AR) features in Indonesian e-commerce platforms. Methodology/approach: The research uses a quantitative approach. The analysis method is SEM-PLS (Structural Equation Modeling - Partial Least Squares). The sample consists of 176 women who have used AR features on Shopee, Tokopedia, Lazada, and Blibli. Key variables include vividness, shopping benefits, behavioral control, satisfaction, and purchase intention. Results/findings: Vividness positively affects both behavioral control and satisfaction. Shopping benefits significantly influence satisfaction. Behavioral control and satisfaction positively impact purchase intention. More realistic and interactive AR features improve user satisfaction and boost buying intention. Conclusion: This study concludes that augmented reality (AR) features in e-commerce significantly influence the purchase intention of cosmetic users in Indonesia. Factors such as vividness, shopping benefits, and behavioral control positively affect satisfaction, which in turn enhances purchase intention. The research fills a gap by linking vividness and shopping benefits with user satisfaction, which leads to actual purchase intentions in AR-based platforms. Limitations: This study only involves users of specific e-commerce platforms, so the results may not be fully representative of all augmented reality features across e-commerce platforms in Indonesia. Contribution: Offers strategic insights for brand owners and marketers to enhance AR-based features. Guides IT and tech developers to build more effective AR experiences. Supports digital marketing practices in the beauty and cosmetics sector.